On the problem of systematics of forcible theft of property in the Criminal Code of the Russian Federation and the Republic of Belarus - Eliseev, Sergey A. (Journal of the Belarusian State University. Law, 2019)
Plunder with of violence, not dangerous to the life or health of the victim, or the threat of such violence, robbery has long been known to Russian and Belarusian criminal laws. The study of the ratio of the compositions of these crimes suggests that there are no rational grounds for differentiation in the Criminal Codes of the Russian Federation and the Republic of Belarus of the forced theft of someone else’s property for plunder with of violence and robbery. The identification of plunder with of violence as a form of theft can only be explained by historical tradition. Plunder with of violence has more in common with robbery than it will distinguish from it. Robbery with violence, as well as robbery, harms not only property relations, but also an additional object – the person. Taking possession of other people’s property by means of physical or mental violence speaks about the same degree of public danger of persons who have chosen such a method of committing a crime against property. This, in fact, was recognized by the legislator himself, who established for committing robbery with violence, plunder close in size to the penalty of imprisonment. «Kinship» of violent robbery with robbery was seen and seen by Russian criminologists. In view of these circumstances, it is proposed to combine in the criminal codes of the Russian Federation and the Republic of Belarus violent plunder and robbery in one composition – «robbery» (perhaps such a name – «plunder»).
Keywords: code; law code; plunder; robbery; theft